Local Wisdom As Social Cohesion Of “Kebhinekaan” The Study Of Hindu-Islamic Relations In Eastern Indonesia - Suparman Jayadi (Jurnal Penelitian Agama Hindu, 2022)
Local wisdom has to serve as a cultural identity, intellectual property and religion if the integrity and diversity of the Indonesian people is to remain. This research analyzes local wisdom as social cohesion of “kebhinekaan” the study of hindu-islamic relations  in Lingsar Village West Lombok, Eastern Indonesia. The Perang Topat tradition carried out by Sasak Moslems and Balinese Hindus is the analytical unit in this qualitative research. After conducting field research through observations, in-depth interviews and documentation, the data gathered was validated by comparing it with multiple sources of evidence. Furthermore, it was analyzed using the ‘Parsons' social integration theory’. The results showed that the Sasak Muslims and Balinese Hindu in Lingsar Village and West Lombok, socially integrated in the form of social practices through the traditions of the Perang Topat. Furthermore, theyco-exist peacefully and maintain similar religious communities and cultures. As at the time of this research, the Perang Topat tradition still exists as a local wisdom and symbol of social cohesion of national diversity.